A preparation process of high-strength crack-resistant plaster
By using hydroxylated glass fibers, nano Ca(OH)2 and silane coupling agents in plaster plaster, combined with refired magnesium oxide and dihydrogen phosphate, the problems of insufficient strength and easy cracking are solved, and high strength and crack resistance are improved.
Patent Information
- Application Number
- CN202411192522.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-08-28
AI Technical Summary
The existing plaster plaster is relatively low in strength, difficult to withstand external loads, and is prone to cracking during water dispersion, which increases the difficulty of subsequent repair.
A high-strength crack-resistant plaster plaster is used to prepare a high-strength crack-resistant plaster plaster. By hydroxylation of glass fibers and combined with nano Ca(OH)2 and silane coupling agent, a glass fiber anti-cracking agent is formed, combining refired magnesium oxide and dihydrogen phosphate to form a struvite hydration product, which improves the strength and crack-resistant properties of plaster plaster plaster.
It significantly enhances the strength and crack resistance of the plastered plaster, improves the adhesion with the wall, prevents fall off and powdering, and reduces cracking during the moisture replenishment process.
Smart Images

Figure CN118771838B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastering gypsum preparation, in particular to a preparation process of high-strength crack-resistant plastering gypsum. Background Art
[0002] Plastering gypsum is a plastering material made of gypsum powder as the main cementing material and admixtures. It is currently widely used to fill cracks, depressions, irregular surfaces on the wall, restore the flatness of the wall, etc., and improve the aesthetics of the wall. In addition, the plastering gypsum layer formed on the wall also has the functions of heat preservation, heat insulation, and sound insulation. However, due to the low strength of the cementing material such as gypsum itself, the strength of the prepared plastering gypsum is also low, and its ability to withstand external loads is poor, and it is easily damaged during service. In addition, the plastering gypsum coated on the wall often loses water quickly during the gelling and hardening process, which causes the plastering gypsum layer to crack, produce microcracks, and increase the subsequent engineering repair amount. Summary of the invention
[0003] In view of the above problems, the present invention provides a preparation process of high-strength crack-resistant plastering gypsum, which not only solves the problem of insufficient strength of plastering gypsum, but also improves the crack resistance of plastering gypsum. Specifically, the technical solution of the present invention is as follows.
[0004] A preparation process of high-strength crack-resistant plastering gypsum comprises the following steps:
[0005] (1) Pre-treating glass fibers in hydrofluoric acid, separating the glass fibers after pre-treatment, and placing them in a mixture of concentrated sulfuric acid and hydrogen peroxide solution for standing, to obtain hydroxylated glass fibers.
[0006] (2) placing the hydroxylated glass fiber in a nano-Ca(OH) 2 The method comprises the following steps: adding the silane coupling agent to ethanol, mixing the mixture evenly, and then sealing and heating to keep the mixture warm. After the mixture is completed, the fibers are separated to obtain the glass fiber anti-cracking agent.
[0007] (3) Take at least the following raw materials: 110-135 parts by weight of gypsum powder, 20-30 parts by weight of the glass fiber anti-cracking agent, 25-50 parts by weight of dead-burned magnesium oxide powder, 8-14 parts by weight of dihydrogen phosphate, 1-3 parts by weight of magnesium bicarbonate, and 5-6.5 parts by weight of retarder. Mix the above raw materials evenly, add water and a water reducing agent, and mix evenly to obtain plaster gypsum.
[0008] Furthermore, in step (1), the ratio of the glass fiber to the hydrofluoric acid is 1 g: 5-20 ml. Optionally, the concentration of the hydrofluoric acid is 1-4.5 mol / L. The length of the glass fiber is not less than 3 mm.
[0009] Furthermore, in step (1), the pretreatment time is 20 to 40 minutes. Pretreatment in hydrofluoric acid helps to increase the roughness and surface area of the glass fiber, which not only helps to increase the bonding force between the fiber and the plaster, but also increases the nano-Ca(OH) 2 Particle loading.
[0010] Furthermore, in step (1), the volume ratio of the concentrated sulfuric acid to the hydrogen peroxide solution is 7:3. Optionally, the mass fraction of the hydrogen peroxide solution is 20-25%.
[0011] Furthermore, in step (1), the standing time is 30 to 45 minutes.
[0012] Furthermore, in step (2), the ratio of the hydroxylated glass fiber to ethanol is 1 g: 20-40 ml.
[0013] Furthermore, in step (2), the nano-Ca(OH) 2 The content is 8~15g / L.
[0014] Furthermore, in step (2), the mass fraction of the silane coupling agent in the ethanol is 0.3-0.6%. Optionally, the silane coupling agent includes at least one of KH550, KH560, KH570, etc.
[0015] Furthermore, in step (2), the heating temperature is 50-70° C., and the insulation time is 1-2 hours.
[0016] Furthermore, in step (3), the dihydrogen phosphate includes at least one of potassium dihydrogen phosphate, ammonium dihydrogen phosphate, etc.
[0017] Furthermore, in step (3), the retarder includes any one of triethanolamine, zinc chloride, etc.
[0018] Furthermore, in step (3), water is added according to a water-cement ratio of 0.5 to 0.8.
[0019] Furthermore, in step (3), the amount of the water reducer added is 1-2% of the gypsum content. Optionally, the water reducer includes at least one of a polycarboxylate water reducer, a lignin sulfonate water reducer, a naphthalene water reducer, and the like.
[0020] The technical solution provided by the present invention has the following beneficial technical effects:
[0021] (1) The plastering gypsum of the present invention contains dead-burned magnesium oxide and dihydrogen phosphate, which react with water to form struvite. This hydration product has high strength and strong adhesion. On the one hand, it is distributed in the plastering gypsum as a skeleton and reinforcing phase, which can not only significantly enhance the strength and hardness, but also improve the adhesion between the plastering gypsum and the wall surface, and prevent it from falling off and powdering. On the other hand, it can also play a good bonding role on the hydration product of gypsum, and enhance the crack resistance of the plastering gypsum matrix.
[0022] (2) The plastering gypsum of the present invention is mixed with a glass fiber anti-cracking agent, and the surface of the glass fiber is loaded with calcium hydroxide. On the one hand, during the hydration and hardening process of the plastering gypsum, the calcium hydroxide reacts with magnesium bicarbonate to form solid particles such as water and calcium carbonate. At the same time, since the reaction of the calcium hydroxide and the magnesium bicarbonate gradually proceeds, water can be replenished during the gelling and hardening stage of the plastering gypsum, thereby preventing the problem of cracking caused by the rapid loss of water in the plastering gypsum in the early stage, which affects the strength of the plastering gypsum layer. On the other hand, the glass fiber itself is anchored in the plastering gypsum and can also play a good role in improving the anti-cracking ability. In addition, the solid particles such as calcium carbonate generated attached to the surface of the glass fiber help to increase the resistance of the glass fiber to be pulled out from the plastering gypsum matrix, thereby increasing the anti-cracking ability of the plastering gypsum. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein:
[0024] Figure 1 The following is a sample diagram of the plastering gypsum dry mix prepared in Example 1.
[0025] Figure 2 The following is a sample diagram of the plaster gypsum slurry prepared in Example 1. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0027] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If not otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. Now, the present invention is further described in conjunction with the accompanying drawings and specific embodiments of the present invention, and the preferred implementation methods and materials described in the present invention are only for demonstration purposes.
[0028] Example 1
[0029] A preparation process of high-strength crack-resistant plastering gypsum comprises the following steps:
[0030] (1) Mix glass fibers with a length distribution between 3 and 5 mm with hydrofluoric acid having a concentration of 4 mol / L at a ratio of 1 g:10 ml and stir for 30 minutes. Then filter out the glass fibers and place them in a mixture of concentrated sulfuric acid and hydrogen peroxide solution (composed of 98% concentrated sulfuric acid and 20% hydrogen peroxide solution in a volume ratio of 7:3) and let them stand for 35 minutes. After completion, hydroxylated glass fibers are obtained and set aside.
[0031] (2) mixing the hydroxylated glass fiber with nano-Ca(OH) 2 Ethanol dispersion (including nano-Ca(OH) 2 The content is 13g / L) is added to a beaker at a ratio of 1g:20ml, and then the silane coupling agent KH550 is added at a ratio of 0.5% of the mass fraction of the silane coupling agent in the ethanol. After stirring evenly, the beaker is sealed with plastic wrap, and then heated to 60°C in a water bath for 1.5 hours. After completion, the fiber is filtered out to obtain the glass fiber anti-cracking agent for standby use.
[0032] (3) Take the following raw materials: 128 parts by weight of gypsum powder, 25 parts by weight of the glass fiber anti-cracking agent of this embodiment, 40 parts by weight of dead-burned magnesium oxide powder, 10 parts by weight of potassium dihydrogen phosphate, 2 parts by weight of magnesium bicarbonate, and 6 parts by weight of triethanolamine. Mix the above raw materials and stir for 5 minutes (the resulting dry mixture is as follows Figure 1 As shown), then add water according to the water-cement ratio of 0.7, and add 1.9 parts by weight of polycarboxylate water reducer, mix and stir for 1 minute to obtain plaster gypsum slurry (as shown Figure 2 as shown).
[0033] According to GB / T 28627-2023 Plastering Gypsum, the absolute dry compressive strength, absolute dry flexural compressive strength and bonding strength of the plastering gypsum slurry prepared in this embodiment are tested. The crack resistance of the plastering gypsum of this embodiment is tested by the following method: a layer of the plastering gypsum with a length, width and height of 300mm×50mm×10mm is applied on the cement board, and then placed in a test environment with a wind speed of 2m / s for 10 hours, and then the cracks on the surface of the plastering gypsum layer are observed. The test results are shown in the following table:
[0034] .
[0035] Example 2
[0036] A preparation process of high-strength crack-resistant plastering gypsum comprises the following steps:
[0037] (1) Mix glass fibers with a length distribution between 4 and 7 mm with hydrofluoric acid having a concentration of 1 mol / L at a ratio of 1 g:20 ml and stir for 40 minutes. Then filter out the glass fibers, place them in a mixture of concentrated sulfuric acid and hydrogen peroxide solution (composed of 98% concentrated sulfuric acid and 20% hydrogen peroxide solution at a volume ratio of 7:3) and let them stand for 45 minutes. After completion, hydroxylated glass fibers are obtained and set aside.
[0038] (2) mixing the hydroxylated glass fiber with nano-Ca(OH) 2 Ethanol dispersion (including nano-Ca(OH) 2 The content is 8g / L) is added into a beaker at a ratio of 1g:30ml, and then the silane coupling agent KH570 is added at a ratio of 0.6% of the mass fraction of the silane coupling agent in the ethanol. After stirring evenly, the beaker is sealed with plastic wrap, and then heated to 50°C in a water bath for 2 hours. After completion, the fiber is filtered out to obtain the glass fiber anti-cracking agent for standby use.
[0039] (3) Take the following raw materials: 135 parts by weight of gypsum powder, 30 parts by weight of the glass fiber anti-cracking agent of this embodiment, 50 parts by weight of dead-burned magnesium oxide powder, 14 parts by weight of ammonium dihydrogen phosphate, 3 parts by weight of magnesium bicarbonate, and 6.5 parts by weight of triethanolamine. Mix the above raw materials and stir for 5 minutes, then add water at a water-cement ratio of 0.8, and add 2.7 parts by weight of sodium lignin sulfonate water reducer, mix and stir for 1 minute to obtain plaster gypsum slurry.
[0040] According to GB / T 28627-2023 Plastering Gypsum, the absolute dry compressive strength, absolute dry flexural compressive strength and bonding strength of the plastering gypsum slurry prepared in this embodiment are tested. The crack resistance of the plastering gypsum of this embodiment is tested by the following method: a layer of the plastering gypsum with a length, width and height of 300mm×50mm×10mm is applied on the cement board, and then placed in a test environment with a wind speed of 2m / s for 10 hours, and then the cracks on the surface of the plastering gypsum layer are observed. The test results are shown in the following table:
[0041] .
[0042] Example 3
[0043] A preparation process of high-strength crack-resistant plastering gypsum comprises the following steps:
[0044] (1) Mix glass fibers with a length distribution between 3 and 5 mm with hydrofluoric acid having a concentration of 4.5 mol / L at a ratio of 1 g:5 ml and stir for 20 minutes. Then filter out the glass fibers and place them in a mixture of concentrated sulfuric acid and hydrogen peroxide solution (composed of 98% concentrated sulfuric acid and 25% hydrogen peroxide solution at a volume ratio of 7:3) and let them stand for 30 minutes. After completion, hydroxylated glass fibers are obtained and set aside.
[0045] (2) mixing the hydroxylated glass fiber with nano-Ca(OH) 2 Ethanol dispersion (including nano-Ca(OH) 2 The content is 15g / L) is added to a beaker at a ratio of 1g:40ml, and then the silane coupling agent KH560 is added at a ratio of 0.3% of the mass fraction of the silane coupling agent in the ethanol. After stirring evenly, the beaker is sealed with plastic wrap, and then heated to 70°C in a water bath for 1 hour. After completion, the fiber is filtered out to obtain the glass fiber anti-cracking agent, which is set aside.
[0046] (3) Take the following raw materials: 110 parts by weight of gypsum powder, 20 parts by weight of the glass fiber anti-cracking agent of this embodiment, 25 parts by weight of dead-burned magnesium oxide powder, 8 parts by weight of ammonium dihydrogen phosphate, 1 part by weight of magnesium bicarbonate, and 5 parts by weight of zinc chloride. Mix the above raw materials and stir for 3 minutes, then add water at a water-cement ratio of 0.5, and add 1.1 parts by weight of polycarboxylate water reducer, mix and stir for 1 minute to obtain plaster gypsum slurry.
[0047] According to GB / T 28627-2023 Plastering Gypsum, the absolute dry compressive strength, absolute dry flexural compressive strength and bonding strength of the plastering gypsum slurry prepared in this embodiment are tested. The crack resistance of the plastering gypsum of this embodiment is tested by the following method: a layer of the plastering gypsum with a length, width and height of 300mm×50mm×10mm is applied on the cement board, and then placed in a test environment with a wind speed of 2m / s for 10 hours, and then the cracks on the surface of the plastering gypsum layer are observed. The test results are shown in the following table:
[0048] .
[0049] Example 4
[0050] A preparation process of high-strength crack-resistant plastering gypsum comprises the following steps:
[0051] (1) Mix glass fibers with a length distribution between 3 and 5 mm with hydrofluoric acid having a concentration of 4 mol / L at a ratio of 1 g:10 ml and stir for 30 minutes. Then filter out the glass fibers and place them in a mixture of concentrated sulfuric acid and hydrogen peroxide solution (composed of 98% concentrated sulfuric acid and 20% hydrogen peroxide solution in a volume ratio of 7:3) and let them stand for 35 minutes. After completion, hydroxylated glass fibers are obtained and set aside.
[0052] (2) mixing the hydroxylated glass fiber with nano-Ca(OH) 2 Ethanol dispersion (including nano-Ca(OH) 2 The content is 13g / L) is added to a beaker at a ratio of 1g:20ml, and then the silane coupling agent KH550 is added at a ratio of 0.5% of the mass fraction of the silane coupling agent in the ethanol. After stirring evenly, the beaker is sealed with plastic wrap, and then heated to 60°C in a water bath for 1.5 hours. After completion, the fiber is filtered out to obtain the glass fiber anti-cracking agent for standby use.
[0053] (3) Take the following raw materials: 128 parts by weight of gypsum powder, 25 parts by weight of the glass fiber anti-cracking agent of this embodiment, 2 parts by weight of magnesium bicarbonate, and 6 parts by weight of triethanolamine. Mix the above raw materials and stir for 5 minutes, then add water according to a water-cement ratio of 0.7, and add 1.9 parts by weight of polycarboxylate water reducer, mix and stir for 1 minute to obtain plaster gypsum slurry.
[0054] According to GB / T 28627-2023 Plastering Gypsum, the absolute dry compressive strength, absolute dry flexural compressive strength and bonding strength of the plastering gypsum slurry prepared in this embodiment are tested. The crack resistance of the plastering gypsum of this embodiment is tested by the following method: a layer of the plastering gypsum with a length, width and height of 300mm×50mm×10mm is applied on the cement board, and then placed in a test environment with a wind speed of 2m / s for 10 hours, and then the cracks on the surface of the plastering gypsum layer are observed. The test results are shown in the following table:
[0055] .
[0056] Example 5
[0057] A preparation process of high-strength crack-resistant plastering gypsum comprises the following steps:
[0058] (1) Mix glass fibers with a length distribution between 3 and 5 mm with hydrofluoric acid having a concentration of 4.5 mol / L at a ratio of 1 g:5 ml and stir for 20 minutes. Then filter out the glass fibers and place them in a mixture of concentrated sulfuric acid and hydrogen peroxide solution (composed of 98% concentrated sulfuric acid and 25% hydrogen peroxide solution at a volume ratio of 7:3) and let them stand for 30 minutes. After completion, hydroxylated glass fibers are obtained and set aside.
[0059] (2) Add the hydroxylated glass fiber and ethanol in a ratio of 1 g:40 ml to a beaker, then add the silane coupling agent KH560 in a ratio of 0.3% by mass fraction of the silane coupling agent in the ethanol, stir evenly and seal the beaker with plastic wrap, then heat in a water bath to 70° C. for 1 hour, filter out the fiber after completion, and obtain the glass fiber anti-cracking agent for standby use.
[0060] (3) Take the following raw materials: 110 parts by weight of gypsum powder, 20 parts by weight of the glass fiber anti-cracking agent of this embodiment, 25 parts by weight of dead-burned magnesium oxide powder, 8 parts by weight of ammonium dihydrogen phosphate, 1 part by weight of magnesium bicarbonate, and 5 parts by weight of zinc chloride. Mix the above raw materials and stir for 3 minutes, then add water at a water-cement ratio of 0.5, and add 1.1 parts by weight of polycarboxylate water reducer, mix and stir for 1 minute to obtain plaster gypsum slurry.
[0061] According to GB / T 28627-2023 Plastering Gypsum, the absolute dry compressive strength, absolute dry flexural compressive strength and bonding strength of the plastering gypsum slurry prepared in this embodiment are tested. The crack resistance of the plastering gypsum of this embodiment is tested by the following method: a layer of the plastering gypsum with a length, width and height of 300mm×50mm×10mm is applied on the cement board, and then placed in a test environment with a wind speed of 2m / s for 10 hours, and then the cracks on the surface of the plastering gypsum layer are observed. The test results are shown in the following table:
[0062] .
[0063] Example 6
[0064] A preparation process of high-strength crack-resistant plastering gypsum comprises the following steps:
[0065] Take the following raw materials: 128 parts by weight of gypsum powder, 25 parts by weight of the glass fiber anti-cracking agent prepared in Example 1, 40 parts by weight of dead-burned magnesium oxide powder, 10 parts by weight of potassium dihydrogen phosphate, and 6 parts by weight of triethanolamine. Mix the above raw materials and stir for 5 minutes, then add water according to a water-cement ratio of 0.7, add 1.9 parts by weight of polycarboxylate water reducer, mix and stir for 1 minute to obtain plaster gypsum slurry.
[0066] According to GB / T 28627-2023 Plastering Gypsum, the absolute dry compressive strength, absolute dry flexural compressive strength and bonding strength of the plastering gypsum slurry prepared in this embodiment are tested. The crack resistance of the plastering gypsum of this embodiment is tested by the following method: a layer of the plastering gypsum with a length, width and height of 300mm×50mm×10mm is applied on the cement board, and then placed in a test environment with a wind speed of 2m / s for 10 hours, and then the cracks on the surface of the plastering gypsum layer are observed. The test results are shown in the following table:
[0067] .
[0068] Example 7
[0069] A preparation process of high-strength crack-resistant plastering gypsum comprises the following steps:
[0070] (1) Glass fibers with a length distribution between 4 and 7 mm are mixed with nano-Ca(OH) 2 Ethanol dispersion (including nano-Ca(OH) 2The content is 8g / L) is added into a beaker at a ratio of 1g:30ml, and then the silane coupling agent KH570 is added at a ratio of 0.6% of the mass fraction of the silane coupling agent in the ethanol. After stirring evenly, the beaker is sealed with plastic wrap, and then heated to 50°C in a water bath for 2 hours. After completion, the fiber is filtered out to obtain the glass fiber anti-cracking agent for standby use.
[0071] (2) Take the following raw materials: 135 parts by weight of gypsum powder, 30 parts by weight of the glass fiber anti-cracking agent of this embodiment, 50 parts by weight of dead-burned magnesium oxide powder, 14 parts by weight of ammonium dihydrogen phosphate, 3 parts by weight of magnesium bicarbonate, and 6.5 parts by weight of triethanolamine. Mix the above raw materials and stir for 5 minutes, then add water at a water-cement ratio of 0.8, and add 2.7 parts by weight of sodium lignin sulfonate water reducer, mix and stir for 1 minute to obtain plaster gypsum slurry.
[0072] According to GB / T 28627-2023 Plastering Gypsum, the absolute dry compressive strength, absolute dry flexural compressive strength and bonding strength of the plastering gypsum slurry prepared in this embodiment are tested. The crack resistance of the plastering gypsum of this embodiment is tested by the following method: a layer of the plastering gypsum with a length, width and height of 300mm×50mm×10mm is applied on the cement board, and then placed in a test environment with a wind speed of 2m / s for 10 hours, and then the cracks on the surface of the plastering gypsum layer are observed. The test results are shown in the following table:
[0073] .
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A preparation process of high-strength crack-resistant plastering gypsum, characterized in that: The steps include: (1) Pre-treating glass fibers in hydrofluoric acid, separating the glass fibers after pre-treatment, and placing the glass fibers in a mixture of concentrated sulfuric acid and hydrogen peroxide solution for standing, to obtain hydroxylated glass fibers; (2) placing the hydroxylated glass fiber in ethanol with a nano-Ca(OH)2 content of 8-15 g / L, then adding a silane coupling agent at a mass fraction of 0.3-0.6% of the silane coupling agent in the ethanol, mixing evenly, sealing and heating to keep warm, and separating the fibers after completion to obtain a glass fiber anti-cracking agent; wherein the ratio of the hydroxylated glass fiber to the ethanol is 1 g: 20-40 ml; the heating temperature is 50-70° C., and the insulation time is 1-2 hours; (3) Take at least the following raw materials: 110-135 parts by weight of gypsum powder, 20-30 parts by weight of the glass fiber anti-cracking agent, 25-50 parts by weight of dead-burned magnesium oxide powder, 8-14 parts by weight of dihydrogen phosphate, 1-3 parts by weight of magnesium bicarbonate, and 5-6.5 parts by weight of retarder; mix the above raw materials evenly, add water and a water reducing agent, and mix evenly to obtain plaster gypsum.
2. The preparation process of the high-strength crack-resistant plaster according to claim 1, characterized in that: In step (1), the ratio of the glass fiber to the hydrofluoric acid is 1 g: 5-20 ml.
3. The preparation process of the high-strength crack-resistant plaster according to claim 1, characterized in that: In step (1), the concentration of the hydrofluoric acid is 1-4.5 mol / L.
4. The preparation process of the high-strength crack-resistant plaster according to claim 1, characterized in that: In step (1), the length of the glass fiber is not less than 3 mm.
5. The preparation process of the high-strength crack-resistant plaster according to claim 1, characterized in that: In step (1), the pretreatment time is 20 to 40 minutes.
6. The preparation process of the high-strength crack-resistant plaster according to claim 1, characterized in that: In step (1), the volume ratio of the concentrated sulfuric acid to the hydrogen peroxide solution is 7:
3.
7. The preparation process of the high-strength crack-resistant plaster according to claim 1, characterized in that: In step (1), the mass fraction of the hydrogen peroxide solution is 20-25%.
8. The preparation process of the high-strength crack-resistant plaster according to claim 1, characterized in that: In step (1), the standing time is 30 to 45 minutes.
9. The preparation process of the high-strength crack-resistant plaster according to claim 1, characterized in that: In step (2), the silane coupling agent includes at least one of KH550, KH560, and KH570.
10. The preparation process of the high-strength crack-resistant plaster according to claim 1, characterized in that: In step (3), water is added according to a water-cement ratio of 0.5 to 0.
8.
11. The preparation process of the high-strength crack-resistant plaster according to any one of claims 1 to 10, characterized in that: In step (3), the dihydrogen phosphate includes at least one of potassium dihydrogen phosphate and ammonium dihydrogen phosphate.
12. The preparation process of the high-strength crack-resistant plaster according to any one of claims 1 to 10, characterized in that: In step (3), the retarder includes any one of triethanolamine and zinc chloride.
13. The preparation process of the high-strength crack-resistant plaster according to any one of claims 1 to 10, characterized in that: In step (3), the amount of the water reducing agent added is 1-2% of the gypsum content.
14. The preparation process of the high-strength crack-resistant plaster according to any one of claims 1 to 10, characterized in that: In step (3), the water reducer includes at least one of a polycarboxylate water reducer, a lignin sulfonate water reducer, and a naphthalene water reducer.
Citation Information
Patent Citations
Water-resistant magnesium phosphate cement and application thereof
CN104591570A
Plastering gypsum and preparation method thereof
CN105130354A